Bacterial glycoproteins: Functions, biosynthesis and applications - Upreti, Raj K.; Kumar, Manoj; Shankar, V. (Proteomics (Weinheim), 2003)
Although widely distributed in eukaryotic cells glycoproteins appear to be rare in prokaryotic organisms. The prevalence of the misconception that bacteria do not glycosylate their proteins has been a subject matter of discussion for a long time. Glycoconjugates that are linked to proteins or peptides, generated by the ribosomal translational mechanism have been reported only in the last two to three decades in a few prokaryotic organisms. Most studied prokaryotic glycoproteins are the S‐layer glycoproteins of Archeabacteria. Apart from these, membrane‐associated, surface‐associated, secreted glycoproteins and exoenzymes glycoproteins are also well documented in both, Archea and Eubacteria. From the recent literature, it is now clear that prokaryotes are capable of glycosylating proteins. In general, prokaryotes are deprived of the cellular organelles required for glycosylation. In prokaryotes many different glycoprotein structures have been observed that display much more variation than that observed in eukaryotes. Besides following similar mechanisms in the process of glycosylation, prokaryotes have also been shown to use mechanisms that are different from those found in eukaryotes. The knowledge pertaining to the functional aspects of prokaryotic glycoproteins is rather scarce. This review summarizes developments and understanding relating to characteristics, synthesis, and functions of prokaryotic glycoproteins. An extensive summary of glycosylation that has been reported to occur in bacteria has also been tabulated. Various possible applications of these diverse biomolecules in biotechnology, vaccine development, pharmaceutics and diagnostics are also touched upon.